FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG PADA MAHASISWA D3 MARKETING - Arum Wahyuni Purbohastuti (FEB Universitas Sultan Ageng Tirtayasa, 2017)
This study aims to determine the factors that influence the purchase decision of Samsung brand mobile brand. Where The object of research is Student D3 Marketing University of Sultan Ageng Tirtayasa force year 2014.The method used in this research is qualitative method that is descriptive research and tend to use analysis. Samples taken were 21 students from 44 students.Based on the research that has been done, the purchase decision of mobile brands among D3 Marketing students is influenced by several factors including brand image, quality, price, features, warranty, access to get, needs, social factors.